La motivación en el proceso de enseñanza aprendizaje en los estudiantes del octavo, noveno y decimo año de educación general básica de la unidad educativa Monseñor Leónidas Proaño, de la parroquia San Luis de Pambil, cantón Guaranda, provincia de Bolívar - Barragán Mora, Washington Fredy (2012)
The present investigation on The motivation in the teaching process and their contribution in the affective social environment of learning in the students of the eighth, ninth and tenth year of basic education of the unit educational monsignor Leonidas Proaño, of the parish San Luis of Pambil, canton Guaranda, county of Bolívar, period 2011 - 2012. ". The primordial objective is to determine the motivation in the affective social environment for the process of teaching learning in the students of the eighth, ninth and tenth year of basic education of the unit educational Monsignor Leonidas Proaño. In this educational unit it has been noticed the limited motivation that you/they impose in their educandos, clearly like one says in the popular jargon, the educational one is who should inject positive energy to their educandos, this makes them to be more active during the processes of teaching learning. Since all teaching process should be planned by means of the educator's daily motivation so that the student feels more attracted of the knowledge This grade work is conformed by a first introductory part, in the one that thinks about the topic, the antecedents, the problem, the justification, objectives, hypothesis and the operacionalización of variables are presented; what corresponds to the general presentation of the work. The chapter I contains the theoretical mark; Here the whole theory related with the investigation topic is developed, considering the three variables of the hypothesis, to be able to determine the causes and effects of the problem and power to carry out the investigation to the educational ones and students; with the purpose of looking for alternative of solution to the problem. The chapter II are integrated by the methodological mark; in the one that you/they are detailed: the investigation type, the methods, the techniques to be used in dhe The chapter III correspond to the analysis of the results obtained in the investigation; here they are presented the statistic in a square and their graphic representation in pastries, to proceed to analyze each one of the questions. What allows to carry out the confirmation of the hypothesis, conclusions and recommendations. The chapter IV refer to the proposal, in her he/she thinks about the title, the introduction, the objectives that love each other to achieve with the proposal, as well as the same development with the positions that are made; and finally the evidence and results of the application of the proposal that it is reflected in the annexes.